Interventional Radiology Procedures of the Shoulder - Fawcett, Richard; Rowbotham, Emma (Seminars in Musculoskeletal Radiology, 2022)
Using imaging guidance to perform procedures around the shoulder girdle has become established practice in musculoskeletal radiology. Whether it be therapeutic injections for intra-articular pathology, rotator cuff or subacromial/subdeltoid bursal pathology, or injections for diagnostic purposes, such as magnetic resonance or computed tomography arthrography, a range of techniques and imaging modalities can be used. This article discusses the techniques for commonly performed procedures.
Keywords: ultrasound; fluoroscopy; corticosteroid; rotator cuff